Effect of Epilepsy Surgery on Associated Autism - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The outcome of pervasive developmental disorder (PDD) in 5 children who underwent epilepsy surgery at 3 to 8 years of age is reported from the Cleveland Clinic Foundation, Cleveland, OH.